Food Adulteration in Pakistan: A Major Threat to Youth's Health and Life: The Foodborn Disease and Heealth Issues (Biological Sciences - PJSIR, 2024)
The recent malpractices in the food industry is one such sad and global trend. The quantum of this menace in Pakistan is such that has given rise a situation labeled as food emergency. The increase in food adulteration coincides with an alarming increase in the number of deaths due to cardiovascular diseases, respiratory tract infections and cancer along with an increase in mental disorders, especially in youth i.e., depression, frustration and lack of concentration. This study aims at establishing how various adulterants elements added erroneously or intentionally are affecting the physical and mental growth of our youth and what policy implementation steps should be taken to safeguard the physical and psychological wellbeing of our future generations. The purpose of this study is to find out to what extent food adulteration is responsible for this trend in the disease index, especially that of the youth. Being a country where 60% of the population is below the average age of twenty five years forming the productive group, it is importance to establish as to why are we facing the challenges of food safety, is it the lack of legislation, execution of laws, lack of awareness of all of these.